Validation of malay version of the theory of planned behavior (TPB) for smoking cessation questionnaire / Nur Aina Afiqah Zainul Asri - Zainul Asri, Nur Aina Afiqah (2019)
Theory of Planned Behavior (TPB) is the study of human intention in order to perform a given behavior rather than in relation to actual performance. To date, the TPB for smoking cessation in Malay version is not validate by content and face validity as a reliable tool to assess smokers to quit from smoking. The aim of this research is to validate the Malay version of the Theory of Planned Behavior (TPB) for smoking cessation via face and content validity and to determine the reliability. This research based on data obtained from survey questionnaire that include the participation ono smokers for face validity and 10 health-care professionals for content validity. The health-care professional reviewed the content for relevancy, representativeness, clarify and comprehension. The reliability of the translated instrument was analysed using the Cronbach's alpha and the content validity was analysed using the Content Validity Index (CVI). The results of the study revealed that the Malay version of the Theory of Planned Behavior (TPB) for smoking cessation questionnaire have acceptable validity with 0.865 of CVI and the reliability is 0.839. As a conclusion, this study provides the valid and reliable tool to assess smokers for smoking cessation.